2015
DOI: 10.1016/j.celrep.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Casein Kinase 1δ Is an APC/CCdh1 Substrate that Regulates Cerebellar Granule Cell Neurogenesis

Abstract: SUMMARY Although casein kinase 1δ (CK1δ) is at the center of multiple signaling pathways, its role in the expansion of central nervous system progenitor cells is unknown. Using mouse cerebellar granule cell progenitors (GCPs) as a model for brain neurogenesis, we demonstrate that the loss of CK1δ or treatment of GCPs with a highly selective small molecule inhibits GCP expansion. In contrast, CK1δ overexpression increases GCP proliferation. Thus, CK1δ appears to regulate GCP neurogenesis. CK1δ is targeted for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 66 publications
0
41
0
Order By: Relevance
“…Knockdown of CK1δ by siRNA or pharmacologically by small molecule inhibitors leads to cell cycle arrest in granule neuron progenitors, suggesting that CK1δ promotes the proliferation of granule neuron progenitors. Cdh1-APC triggers the ubiquitination and consequent degradation of CK1δ in granule neuron progenitors (Penas et al 2015), suggesting that Cdh1-APC might promote cell cycle exit and consequent granule neuron differentiation. Surprisingly, however, conditional knockout of Cdh1 in granule neuron progenitors fails to alter the development of the mouse cerebellum even though this leads to increased levels of CK1δ in these cells (Penas et al 2015).…”
Section: Control Of Neurogenesis and Gliogenesis By Cdh1-apcmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of CK1δ by siRNA or pharmacologically by small molecule inhibitors leads to cell cycle arrest in granule neuron progenitors, suggesting that CK1δ promotes the proliferation of granule neuron progenitors. Cdh1-APC triggers the ubiquitination and consequent degradation of CK1δ in granule neuron progenitors (Penas et al 2015), suggesting that Cdh1-APC might promote cell cycle exit and consequent granule neuron differentiation. Surprisingly, however, conditional knockout of Cdh1 in granule neuron progenitors fails to alter the development of the mouse cerebellum even though this leads to increased levels of CK1δ in these cells (Penas et al 2015).…”
Section: Control Of Neurogenesis and Gliogenesis By Cdh1-apcmentioning
confidence: 99%
“…3A; Penas et al 2015). Knockdown of CK1δ by siRNA or pharmacologically by small molecule inhibitors leads to cell cycle arrest in granule neuron progenitors, suggesting that CK1δ promotes the proliferation of granule neuron progenitors.…”
Section: Control Of Neurogenesis and Gliogenesis By Cdh1-apcmentioning
confidence: 99%
“…Furthermore, it has been shown that casein kinase 1 (ck 1) δ is an APC/C-Cdh1 substrate and that it regulates neurogenesis in cerebellar granule cells [32]. The ck 1 family is highly conserved in eukaryotes and controls a broad spectrum of biological processes, e.g., circadian rhythms, signal transduction, apoptosis, and neurite outgrowth.…”
Section: Apc/c-cdh1 and Neurogenesismentioning
confidence: 99%
“…5 Utilizing a cell based screening approach where we expressed Wee1-luciferase in HeLa cells and incubated the transfected cells with small molecule inhibitors, we discovered kinase inhibitors that were selective for Casein kinase (CK)1. 6,7 Using both biochemical and genetic studies we then demonstrated that CK1 and GSK3 phosphorylate Wee1 to target it for destruction. 6,7 In a similar manner, using a p27 Kip1 -luciferase fusion construct we demonstrated that PKCa phosphorylates p27 Kip1 and affects its degradation rate.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Using both biochemical and genetic studies we then demonstrated that CK1 and GSK3 phosphorylate Wee1 to target it for destruction. 6,7 In a similar manner, using a p27 Kip1 -luciferase fusion construct we demonstrated that PKCa phosphorylates p27 Kip1 and affects its degradation rate. 8 One of the main conclusions from these studies is that parallel screening of luciferase fusion proteins incubated with small molecules can uncover upstream modulators of a specific substrate's turnover.…”
Section: Introductionmentioning
confidence: 99%